Opportunities and challenges for herbaria in studying the spatial variation in plant functional diversity. Issue 4 (19th May 2021) - Harris, Timothy; Mulligan, Mark; Brummitt, Neil
Abstract : Herbaria are renowned as collections of specimens for research in plant taxonomy, plant identification and more recently in plant phylogenetics. The production of Floras and monographs in herbaria is fundamental to the understanding of plant taxonomy and plant biogeography. Herbaria have played an important role in providing the raw geographic data behind plant species distributions which form the basis of the most commonly used biodiversity metric: species richness. Less well recognised is the potential for using comprehensive species checklists, produced by herbaria, as a sampling frame when projecting biodiversity metrics. Functional diversity metrics derived from plant trait values are growing in importance in biodiversity monitoring; however, it is unclear whether the trait-based functional attributes are responsive to changes in species richness in all geographic areas. Modelling of the spatial distribution of trait values is one way to investigate the limits of biodiversity monitoring reliant on trait values. The research outputs of herbaria are arguably an untapped resource of such trait data. Greater digitisation of published Flora treatments as well as continuing digitisation of herbarium specimens is increasingly making these resources more available. With appropriate methods to ameliorate known biases in the species locality and plant trait data held by herbaria, these institutions can play an important role in building spatial models of plant trait distributions. Such models help to establish the relationships between species richness and plant functional diversity metrics in different biomes required for trait-led biodiversity monitoring. Here we present a six-step method to allow data held by herbaria to be used to establish a spatial model of functional diversity metrics at a continental scale.